Responsive adjustment of feed-in tariffs to dynamic PV technology development - Thilo Grau (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper reviews the adjustments of the feed-in tariff for new solar photovoltaics (PV) installations in Germany. As PV system prices declined rapidly over the last years, the German government implemented automatic mechanisms to adjust the support level for new installations in response to deployment volumes. This paper develops an analytic model to simulate weekly installations of PV systems ?30 kW (35% market share in 2010) based on project profitability and duration. The model accurately replicates observed market developments, showing the need for (i) more frequent tariff reductions (ii) and an appropriate choice of adjustment response parameters. The model can be used to test for appropriate parameter choices, and to compare different policy designs. To illustrate this, the competing proposals that had been discussed in 2011 are simulated. A robust choice must perform well against multiple scenarios for future PV system prices. The analysis shows that adjustment schemes with more frequent tariff reductions would have reached deployment targets in 2011 more effectively.
Keywords: O30; O31; Q42; Q48; 330; feed-in tariff; photovoltaic; renewable deployment